CUSTOMER TRUST AND COMMITMENT IN INSURANCE: THE MEDIATING ROLE OF SATISFACTION AND LOYALTY" - Zhang, Ming; Chen, Li Wei (International Journal of Allied Research in Marketing and Management (IJARMM), 2023)
In the contemporary business landscape, the viability and prosperity of enterprises are intricately linked to their customer relationships. Sustaining current patrons and acquiring novel clientele have emerged as pivotal drivers of business expansion, particularly within intensely competitive realms, further compounded by their resource-intensive nature. Amid this context, an imperative arises for industries to not only nurture customer loyalty but also to embrace a progressive enhancement approach to ensure customer contentment. This underscores the fundamental necessity for industries to systematically reassess and reevaluate customer requisites in alignment with their needs, thereby engendering satisfaction and ultimately engendering customer retention. In this pursuit, businesses need to strike a harmonious equilibrium between the pursuit of new customers and the fortification of existing relationships, heralding a symbiotic path to enduring success.